Aspek Hukum Dalam Penggunaan Obat-Obatan Terlarang di Bidang Medis Berdasarkan Undang-Undang Nomor 35 Tahun 2009 (International Forum of Researchers and Lecturers, 2025)
Law Number 35 of 2009 concerning Narcotics in Indonesia provides a strong legal basis for regulating the use of narcotics in the medical field. This regulation aims to ensure that the use of narcotics is carried out safely, in a controlled manner and in accordance with the interests of health services. This research aims to analyze legal aspects related to the use of illegal drugs in the medical field, identify challenges in implementing regulations, and provide policy recommendations to overcome existing obstacles. The research method used is normative juridical, with a legal approach and literature studies from various legal and health journals. The research results show that although regulations have been prepared comprehensively, their implementation in the field faces obstacles, such as complicated bureaucracy, lack of education for medical personnel, and social stigma against narcotics use. This hampers patient access to treatment, especially for palliative therapy needs and chronic pain management. The conclusions of this research emphasize the need for strategic steps to increase understanding of medical personnel, simplify administrative procedures, and educate the public to reduce stigma. Thus, existing regulations can be implemented optimally to support public health goals without ignoring aspects of supervision. It is hoped that this recommendation can strengthen the legal system and health services in Indonesia, so that patients' rights to health can be fulfilled more effectively.